Enterprise Risk Management Sebagai Strategi untuk Meningkatkan Kinerja Perusahaan Asuransi - Khenia Erfira Melianita; Alssya Vadhyara Susanto; Almira Dyah Karima; Suhailah Salma; Revaldo Revaldo; Salsabila Az Zahra; Dewi Hanggraeni (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study was conducted to examine the relationship between the level of Enterprise Risk Management (ERM) implementation and corporate performance among insurance companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The Enterprise Risk Management Index (ERMI) was used to assess the level of ERM implementation based on disclosures in the companies’ annual reports. Company performance was assessed using Return on Assets (ROA) as a financial performance indicator and Tobin’s Q as a market performance indicator, with firm size and leverage serving as control variables, and employing a panel data regression method. The results indicate that companies with higher levels of ERM implementation tend to exhibit more effective financial performance, as evidenced by the positive and significant effect of ERMI on ROA. However, the effect of ERMI on Tobin’s Q shows a negative and significant influence, indicating that the market is influenced by the dynamics of the insurance industry and the market in Indonesia. These results demonstrate that the implementation of ERM has a positive impact on improving a company’s internal performance compared to the market’s negative assessment. This study concludes by providing evidence regarding the relationship between ERM implementation and corporate performance within the context of the insurance industry in Indonesia